Independent National Electoral Commission (INEC) and campaign financing monitoring in Nigeria: The 2015 general elections - Sule, Babayo; Mohd Sani, Mohd Azizuddin; Mat, Bakri (2017)
Propose - The Independent National Electoral Commission (INEC) is the electoral umpire responsible for the conduct of general elections in Nigeria and other related electoral activities since the resurgence of democratic rule in 1999. One of these important electoral activities carried out by INEC is campaign monitoring and political party financing activities as provided in the Nigerian Constitution and 2010 Electoral Act. This paper examined the role of INEC in monitoring candidates and parties’ expenditure during the 2015 General Elections. The major problem is the way parties and candidates violated the regulations while INEC as the monitoring body was watchful without any concrete action.